Luminescent Ln3+-based silsesquioxanes with a β-diketonate antenna ligand: toward the design of efficient temperature sensors - Félix, Gautier; Kulakova, Alena N.; Sene, Saad; Khrustalev, Victor N.; Hernández-Rodríguez, Miguel A.; Shubina, Elena S.; Pelluau, Tristan; Carlos, Luís D.; Guari, Yannick; Carneiro Neto, Albano N.; Bilyachenko, Alexey N.; Larionova, Joulia (Frontiers in Chemistry, 2024)
We report the synthesis, single-crystal X-ray diffraction, magnetic, and luminescence measurements of a novel family of luminescent cage-like tetranuclear silsesquioxanes (PhSiO1.5)8(LnO1.5)4(O)(C5H8O2)6(EtOH)2(CH3CN)22CH3CN (where Ln = Tb, 1, Tb/Eu, 2, and Gd, 3), featuring seven-coordinated lanthanide ions arranged in a one-capped trigonal prism geometry. Compounds 1 and 2 exhibit characteristic Tb3+ and Tb3+/Eu3+-related emissions, respectively, sensitized by the chelating antenna acetylacetonate (acac) ligands upon excitation in the UV and visible spectral regions. Compound 3 is used to assess the energies of the acac ligand’s triplet states. For 1, theoretical calculations on the intramolecular energy transfer and multiphonon rates indicate a thermal balance between the 5D4 Stark components, while the mixed Tb3+/Eu3+analog 2, with a Tb:Eu ratio of 3:1, showcases intra-cluster Tb3+-to-Eu3+ energy transfer, calculated theoretically as a function of temperature. By utilizing the intensity ratio between the 5D47F5 (Tb3+) and 5D07F2 (Eu3+) transitions in the 11 ─ 373 K range, we demonstrate the realization of a ratiometric luminescent thermometer with compound 2, operating in the 11–373 K range with a maximum relative sensitivity of 2.0 %K-1 at 373 K. These findings highlight the potential of cage-like silsesquioxanes as versatile materials for optical sensing-enabled applications.